Analisis Koordinasi Relai Proteksi Transformator I 150/20kV GI Bumicokro Akibat Uprating Daya 50MVA Menjadi 60MVA - Anang Dasa Novfowan; Mochammad Mieftah; Heri Sungkowo (Politeknik Negeri Malang, 2023)
Nowadays, Electricity is a important thing for people. As the load grown at the Bumicokro Substation, transformer I had replaced from 50 MVA to 60MVA. Because of that, the relays protection had to be resetting because of the changes of nominal current. Therefore, the objectives of this research are calculated and simulated the setting of OCR (Over Current Relay), GFR (Ground Fault Relay), SBEF (Stand by Earth Fault), differential and REF (Resistance Earth Fault) relay. ETAPv12.6 software is used to get the relay coordination Outgoing 22kV, Incoming 150kV, OCR (Over Current Relay), GFR (Ground Fault Relay), SBEF (Stand by Earth Fault), differential and REF (Resistance Earth Fault) after the calculation and simulation finished, then the result indicated the appropriate conditions to overcome the distrubance at the transformer according to the protection zone. The result of current setting for Differential relay is 2,88A, Primary REF is 0,5A, Secondary REF is 1,1A, 150kV OCR is 3,5A, and the moment setting is 28A, 22kV OCR 150kV 4,7A, GFR 1,44A, SBEF 1,0A. While, the result of time setting for Differential relay, Primary REF, Secondary REF are instant, for 150kV OCR is 1,06s, 22kV OCR is 1,07s, GFR 1,51s, and SBEF 8,8s.